Improving multimodal integation:|bExploring a scenario domain approach - Lee, Cynthia Poh Choo (Universiti Malaysia Sarawak, (UNIMAS), 2012)
Exploring a scenario"domain approach to improve multimodal integration involved speech and sketch in determining the scenario categories of point"to"point, description and query-based. Sketch or speech alone cannot give a clear explanation about a location especially if it is need to go from one place to the others. Objective of this research is to determine the accuracy of predicting different scenario categories based on speech, sketch as well as both speech and sketc~ When both speech and sketch results are combined, the accuracy of prediction is higher compared to solely using speech or sketch only. Overall, the result of the prediction accuracy shows that point-to"point and description scenario categories seem to give a better result compare to query-based scenario category